The Script Work in the Complex Object of Copyrights - Hazieva, Guzel B. (2018)
In article the questions connected with features of the civil mode of the scenario work as a part of difficult objects of author's rights, such as audiovisual works are investigated (movies, film formats and others). The author in detail considers questions of concepts of the scenario work and a difficult object of author's rights. At the same time the special-purpose character of creation of the scenario work as object of an author's right, namely, for use as a part of difficult objects of author's rights reveals, the interconditionality of concepts, existence of two-level system of author's rights concerning a difficult object, namely, the rights for a difficult object, and the rights to results of intellectual activity which were used during creation of a difficult intellectual property item is proved.